PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBINA KOMPETENSI SOSIAL (PELAYANAN PRIMA) TENAGA ADMINISTRASI SEKOLAH - Yuliani, Tri; Kristiawan, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2016)
a quality service is an important point of administration staff in school. A good service gives more satisfaction to the customers. This study used qualitative approach to explore the stakeholdersâ€™ competence in school in advising social competence (quality service). This research focused on administration staff that give quality service to the customers. The data were collected through observation and interview. The data analyisis of this research used Miles & Hubermanâ€™s model. The results revealed that administration staff needs training and educational program to improve the competence. Â Keyword: Leadership, Headmaster, Training and Education, Administration Staff, Quality Service.